SOLID STATE INTERACTION BETWEEN AMOXICILLIN TRIHYDRATE AND POTASSIUM CLAVULANATE - SLAMET IBRAHIM; SUNDANI NURONO SOEWANDHI; SUKMADJAJA ASYARIE; ILMA NUGRAHANI (Universiti Sains Malaysia, 2007)
The aim of this research was to evaluate solid state interaction between amoxicillin trihydrate andpotassium clavulanate. The interaction was observed by Differential Scanning Calorimeter (DSC),X-Ray Powder Diffractometer (XRPD), Fourier Transforms Infra Red (FTIR) and ScanningElectron Microscope (SEM). Mixtures of amoxicillin trihydrate and potassium clavulanate wereprepared in molar ratios of 0:10, 1:9, 2:8, 3:7, 4:6; 5:5; 6:4; 7:3; 8:2; 9:1; 10:0 and analyzed byDSC to obtain the thermal profile and a phase diagram. From this phase diagram, the molar ratiopoint of interaction was determined. XRPD analysis was performed to check the type of physicalinteraction occurred and FTIR was conducted to predict the chemical mechanism of interaction.Thermo profile obtained by DSC analysis of the binary systems showed that endothermic curves ofmolar fractions of 1:9-5:5 overlapped at 201°C. On the other hand, the diffractogram obtainedfrom Powder X-Ray analysis was very similar with that of amoxicillin trihydrate alone. FTIRspectrum of binary system in the molar ratio of 5:5 showed the loss of hydrate spectra fromamoxicillin trihydrate. We conclude that the interaction involved strong hydrogen bondingbetween hydrates of amoxicillin with potassium clavulanate which produced a co-crystal systemlike a solid dispersion.